Bioactive compounds in childhood obesity and associated metabolic complications: Current evidence, controversies and perspectives - Fiore, Giulia; Pascuzzi, Martina Chiara; Di Profio, Elisabetta; Corsello, Antonio; Agostinelli, Marta; La Mendola, Alice; Milanta, Chiara; Campoy, Cristina; Calcaterra, Valeria; Zuccotti, Gianvincenzo; Verduci, Elvira (Pharmacological research, 2023)
Obesity represents the most frequent chronic disease among children worldwide, with a significant global burden on society. Metabolically unhealthy obesity (MUO) can affect children since their first years of life, and novel therapeutic strategies to tackle metabolic complications are under investigation. This review focuses on bioactive compounds and their possible beneficial effects on obesity, particularly omega-3, docosahexaenoic acid, vitamin D, biotics, polysaccharide macromolecules, polyphenols, inositols, alpha lipoic acid, and bromelaine. Our aim is to summarize current evidence about bioactive compounds in the treatment of obesity, highlighting recent findings on their use in children and adolescents. Most studied molecules are omega-3 and vitamin D, despite the heterogeneity between the studies. Moreover, given the emerging interest in the gut-brain axis in the link between metabolic health and microbiota, various studies on prebiotics, probiotics, synbiotics, postbiotics and polysaccharide macromolecules have been considered. Some preclinical studies seem to highlight a possible role of the polyphenols, even if their clinical evidence is still discussed. Lastly, we describe possible effects of inositols and alpha-lipoic acid. Despite some dietary supplements seem to be promising in overweight subjects, only in a few of them a dose/response efficacy has been found in the pediatric age. Innovative, well-designed and targeted clinical trials are then needed to prove the beneficial effects of these compounds that could support the standard behavioral therapy for obesity.